Analisa Pengaruh Main Pressure Tank Cellar dalam Proses Discharge Semen di MV. Cepat - Hidayat, Ihsan; Anwar, Amthori; Noviarianto, Noviarianto (Jurnal Maritim Polimarin, 2024)
Discharge activities on a cement vessel can’t be separated from the discharge pneumatic system, because the bulk cement contained in the cellar tank must be pressurized so that the cement turns into dust and can be unloaded into the land sillo. Failure of the pneumatic system will pose a risk of time delays and losses for the company because it can’t carry out load discharge activities. When the cement discharge activity takes place, there are many problems with the pneumatic system due to the decrease in wind pressure. The purpose of this study was to determine the factors, impacts and efforts made to analyze the effect of main pressure on the cellar tank in the cement discharge process to reduce the risk of delays in cement discharge activities. This study used descriptive qualitative method. Where is described and explained each problem with a detailed explanation. Data collection techniques with the method of observation, interviews with the chief officer and supported by the method of documentation. Damage to the pneumatic valve system causes reduced pressure in the cellar tank to be a factor in the decrease in main pressure. The impact of decreasing main pressure causes cement discharge activities to not be carried out optimally and can even hinder cement discharge activities. The conclusion obtained is that efforts need to be made to improve the skills of the crew on the operation of the pneumatic system and control, routines for the maintenance of the pneumatic system equipment according to the system maintenance plan.